Some observations on operatic singer’s intonation - Sundberg, Johan (Interdisciplinary Studies in Musicology, 2018)
Fundamental frequency (Fo) patterns are analysed in six recordings of the Romance from the First Act of Guiseppe Verdi’s opera Aida. Two of the recordings were sung by the late Swedish tenor Jussi Björling and the remaining four by other international premiere tenors. Fo tracking was carried out semi-automatically using the autocorrelation program of the Soundswell Signal Workstation™ software. Intonation characteristics were measured in relation to equally tempered tuning (ETT) based on the tuning of the orchestra. Great individual differences are found. The mean deviation from ETT varied between - 15 cent and + 30 cent. Only Björling tended to increasingly sharpen intonation, the higher he sang in his passagio region. Moreover, in the long sustained high note at the end of the Recitative he added a Portamento at the end, while the other singers increased Fo by about 40 cent over the same tone. Vibrato rate and extent were similar among the singers, but spectrum analysis of the vibrato waveform revealed various differences. The final descending octave interval exceeded the 2:1 frequency ratio in all singers except one. The results are discussed from the points of view of interval perception, performance practise and musical expression.